2011
DOI: 10.1111/j.1537-2995.2011.03425.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of nanofiltration efficacy in reducing infectivity of centrifuged versus ultracentrifuged 263K scrapie‐infected brain homogenates in “spiked” albumin solutions

Abstract: These findings confirm the utility of nanofiltration in removing infectivity from plasma (or other products) spiked with scrapie brain homogenate supernatants. However, efficiency is diminished using supernatants that have been ultracentrifuged to reduce aggregated forms of the infectious agent. Thus, filtration removal data based on experiments using "standard" low-speed centrifugation supernatants might overestimate the amount of prion removal in plasma or urine-derived therapeutic products.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 63 publications
3
23
0
Order By: Relevance
“…Collectively, these findings are in line with the biological properties of both S HS and plasma [9]. They suggest that the concentration of PrP Sc in the blood could be higher than reported levels.…”
Section: Soluble and Insolublesupporting
confidence: 88%
See 4 more Smart Citations
“…Collectively, these findings are in line with the biological properties of both S HS and plasma [9]. They suggest that the concentration of PrP Sc in the blood could be higher than reported levels.…”
Section: Soluble and Insolublesupporting
confidence: 88%
“…Lacroux et al [24] recently confirmed this possibility when they found that plasma from scrapie-infected sheep was still efficiently infectious after leukodepletion. Evidence-based studies have revealed that soluble prion infectivity is also present in the central nervous system and that it has a biophysical profile similar to that of the peripheral plasma-associated infectivity [5,9,10]. These studies showed that this neuronal infectivity is associated with an aqueous fraction of scrapie-infected hamster brain homogenate termed S HS .…”
Section: Introductionmentioning
confidence: 94%
See 3 more Smart Citations